Project x: yum - Hughes, Monica (Oxford University Press Karachi, 2009)
yum is a fun and engaging story that centers around a group of friends who embark on a culinary adventure. As they experiment with cooking and exploring new flavors, they accidentally create a dish that has unexpected magical properties. This leads to humorous and chaotic situations as they navigate the consequences of their culinary creation. The story highlights themes of friendship, creativity, and the joy of cooking, ultimately showing how food can bring people together in surprising ways.